Uma infraestrutura de experimentação para pesquisa e desenvolvimento em Blockchains e Web3 - Campos, Luiz Eduardo Folly de; Gomes, Reinaldo Cézar de Morais (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2025: Anais Estendidos do XXXI Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2025.16401, 2025)
Trust on the internet is an essential pillar for online interactions, and blockchain technologies offer a new paradigm of trust based on data integrity and decentralization, enabling innovative solutions such as theWeb3 applications. This paper presents the experimental infrastructure for blockchain research and development currently being built within the ILIADA project at RNP, and its use for the development of new Web3 applications.